2021
DOI: 10.3390/nano11071756
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Optimization of Poly-d-Lysine as a Non-Natural Cationic Polypeptide for Gene Transfer in Neuroblastoma Cells

Abstract: Cationic polypeptides and cationic polymers have cell-penetrating capacities and have been used in gene transfer studies. In this study, we investigate the capability of a polymer of D-lysine (PDL), a chiral form of α-Poly-lysine, as a possible nonviral vector for releasing genetic materials to neuroblastoma cells and evaluate its stability against proteases. We tested and compared its transfection effectiveness in vitro as a vehicle for the EGFP plasmid DNA (pDNA) reporter in the SH-SY5Y human neuroblastoma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Finally, it was reported that poly-D-lysine (DPL) conjugates showed higher transfection capacity than PLL ones, as they were more stable for both lysosomal and peptidase degradation [70].…”
Section: Polymeric Carriers 221 Poly(l-lysine) (Pll)mentioning
confidence: 99%
“…Finally, it was reported that poly-D-lysine (DPL) conjugates showed higher transfection capacity than PLL ones, as they were more stable for both lysosomal and peptidase degradation [70].…”
Section: Polymeric Carriers 221 Poly(l-lysine) (Pll)mentioning
confidence: 99%
“…Under the treatment of MXD3 ASO-SPIO NP complex, MXD3 expression was down-regulated and apoptosis was significantly induced in NB cells. Miguel et al identified D-lysine polymer as an effective gene delivery vehicle and could be used as a synthetic cell-penetrating peptide for gene therapy in the SH-SY5Y cell ( Sanchez-Martos et al, 2021 ). Another study found that rabies virus glycoprotein peptide-modified poly D, L-lactide-co-glycolide NPs could specifically target NB in vitro and in vivo and significantly inhibited tumor growth in a mouse model ( Lee et al, 2016b ).…”
Section: Nanotechnology Enhances Therapeutic Treatment For Neuroblastomamentioning
confidence: 99%